Pengaruh CR dan DER Terhadap ROA Pada Perusahaan Perkebunan Kelapa Sawit - ayu; Purboyo; Siti Mardah (Advantage: Journal of Management and Business, 2026)
Abstract Uncertain global market conditions that trigger fluctuations in palm oil commodity prices require the management of plantation companies listed on the Indonesia Stock Exchange (IDX) to be more careful in managing their financial ratios. This study aims to examine and analyze the effect of the Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Assets (ROA). This study uses a quantitative approach, with the population referring to all palm oil plantation companies listed on the IDX for the period 2022-2025. Sampling was conducted using purposive sampling, while hypothesis testing was conducted using multiple linear regression techniques using SPSS version 23. The results of this study conclude that the hypothesis test results state that partially the CR variable shows a negative direction and does not significantly affect ROA, partially the DER variable has a significant negative effect on ROA, while the CR and DER variables simultaneously have a significant effect on ROA. Companies should focus more on tightly controlling the debt portion and streamlining current assets to maintain stable profitability. Keywords: Current Ratio, Debt to Equity Ratio, Return on Assets, Palm Oil Plantations Abstract Ketidakpastian kondisi pasar global yang memicu fluktuasi harga komoditas kelapa sawit menuntut manajemen perusahaan perkebunan di bursa efek indonesia (BEI) untuk lebih berhati-hati dalam mengelola rasio keuangan mereka. Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh Current Ratio (CR) dan Debt to Equity Ratio (DER) terhadap Return on Assets (ROA). Penelitian ini menggunakan pendekatan kuantitatif, populasi merujuk seluruh perusahaan perkebunan kelapa sawit di BEI periode 2022-2025. Pengambilan sampel menggunakan purposive sampling, sementara pengujian hipotesis diolah melalui teknik regresi linier berganda dengan aplikasi SPSS versi 23. Hasil penelitian ini menyimpulkan bahwa hasil uji hipotesis yang menyatakan secara persial variabel CR menunjukan arah negatif dan tidak berpengaruh signifikan ke ROA, secara persial variabel DER berpengaruh negatif signifikan ke ROA, sedangkan variabel CR dan DER secara simultan berpengaruh signifikan terhadap ROA. Perusahaan untuk lebih fokus pada pengendalian porsi hutang secara ketat serta mengefisiensikan aset lancar demi menjaga stabilitas profitabilitas. Keywords: Current Ratio, Debt to Equity Ratio, Return on Assets, Perkebunan Kelapa Sawit